STRETCHING EXERCISE THERAPY AS A NON-PHARMACOLOGICAL NURSING INTERVENTION FOR ACTIVITY INTOLERANCE IN HYPERTENSIVE PATIENTS: A CASE STUDY FROM A RURAL AGRICULTURAL COMMUNITY IN INDONESIA - Fatmala Fathul Huda; Bagus Dwi Cahyono; Evy Aristawati; Nurul Huda; Apriana Rahmawati; Ronal Surya Aditya (Department of Nursing, Faculty of Medicine, Universitas Sriwijaya, 2025)
Activity intolerance, characterized by fatigue, dyspnea, and reduced exercise capacity, is a common nursing diagnosis among patients with hypertension, particularly in rural farmers whose livelihoods require sustained physical labor. In resource limited settings such as Indonesia’s agricultural communities, non pharmacological nursing interventions play a critical role in managing functional impairment associated with uncontrolled hypertension. This case study describes the successful implementation of Stretching Exercise Therapy as a nurse led, home based intervention for Mr. S, a 67 year old farmer with hypertension from Pasuruan, East Java, who presented with activity intolerance manifested by dizziness, leg cramps, and exertional dyspnea. During a three day intervention period, the patient received supervised static stretching sessions lasting 5 to 10 minutes, administered twice daily and targeting major muscle groups. Vital signs and subjective symptoms were monitored before and after each intervention session. Following the intervention, Mr. S demonstrated marked clinical improvement. Blood pressure decreased from 160 over 103 mmHg to 137 over 84 mmHg, heart rate declined from 115 to 84 beats per minute, and all reported subjective symptoms resolved. The patient reported restored energy, improved mobility, and increased confidence in performing daily activities, including light farming tasks. The intervention was safe, cost free, and easily adopted by both the patient and his family. Although this evidence is derived from a single case, the findings suggest that Stretching Exercise Therapy may represent a feasible and low intensity strategy for nurses to address activity intolerance in rural populations with hypertension. Further studies with larger samples and longer follow up periods are needed to confirm efficacy and sustainability.